Relationship between patient ethnicity and prevalence of anemia during pregnancy and the puerperium period and compliance with healthcare recommendations - implications for targeted health policy - Enav Yefet; Avishag Yossef; Manal Massalha; Abeer Suleiman; Aliza Hatokay; Moria Kamhine-Yefet; Zohar Nachum (BMC, 2020)
Abstract Background Anemia is common during pregnancy and the puerperium. The association of ethnicity as well as other characteristics with anemia and compliance with healthcare recommendations has not been studied sufficiently and needs to be explored in order to implement a targeted health policy. We examined the association between ethnicity and the risk for prenatal and puerperium anemia and the compliance with healthcare recommendations. This effort aims to guide reforms in policies and practices that will assist in decreasing anemia prevalence in Israel. Methods This study was a secondary analysis of a prospective cohort study database including 1558 women who delivered vaginally at Emek Medical Center. Anemia was assessed before delivery by obtaining a complete blood count (CBC). After delivery, CBCs were taken in cases of postpartum hemorrhage, symptoms consistent with anemia, prenatal anemia or other clinical indications. The study population was divided according to their ethnicity (Jews and Arabs). The primary outcomes were anemia before delivery, anemia in the immediate postpartum and 6 weeks postpartum, and compliance with healthcare recommendations, which was defined as the rate of women who performed a routine CBC test 6-weeks-postpartum. Results The rates of anemia before delivery and in the puerperium period were similar between Jews and Arabs (before delivery: 88 (11%) versus 98 (14%); 6 weeks postpartum: 55 (21%) vs 68 (28%), respectively;p > 0.05). Iron supplementation was high in both groups during pregnancy (~ 90%) and lower during the postpartum for Jews compared to Arabs (72% vs 83%,respectively; P < .0001). Only one third of the patients performed a CBC 6-weeks-postpartum regardless of ethnicity. Conclusion Overall compliance with health recommendation was high during pregnancy but low postpartum and was reflected in anemia persistence regardless of ethnicity. Because of the adverse long term impact of anemia on patient's health, new policies need to be developed to improve patient's compliance postpartum. A possible strategy is to combine the follow-up of the mother with the one of the newborn in the family health stations (Tipat Halav) and the community clinics similarly to the close follow-up during pregnancy. Additional methods may include active summoning for CBC test and assuring iron supplement consumption.